Children with Intellectual Disabilities and Special School Education in Ghana. Issue 3 (4th May 2018) - Kassah, Bente Lilljan Lind; Kassah, Alexander Kwesi; Phillips, Deborah
Abstract: Even though Ghana has embraced international calls for mainstream education, many children with intellectual disabilities still receive education in segregated special schools. This article discusses the views of seven informants on the importance of special schools in Ghana. After securing the consent of our informants, we conducted in-depth qualitative interviews, transcribed and subjected the data to thematic analysis. The following views on the education of children with intellectual disabilities in special schools emerged; availability of dedicated teachers, variations in learning activities, playing the preparatory role, inclusion on their premises, discrimination and cultural stereotypes. The findings indicate that special schools still play important roles in the education of children with intellectual disabilities in Ghana.